KESEJAHTERAAN KELUARGA PEDAGANG KECIL DI PASAR SENIN DESA RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Apriani, Tuti; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Pasar Senin of Rantau Panjang Kiri Village Rokan Hilir Village. The issue of family welfare through small traders at pasar senin Rantau Panjang Kiri Village was chosen as a background for this research baecause welfare was not a goal of a particular society, buat all societies need prosperity to sustain life in terms of economy, development, mental and physical. The welfare of the family can be seen from 8 indicators, which were: Revenue, Housing / Housing, Clothing, Food, Education, Health, Recreation, and Savings. The purpose of this research was to determain the walfare of small trader family at Pasar Senin of Rantau Panjang Kiri Village and to know the factors that affect the welfare of small traders families in Pasar Senin Rantau Panjang Kiri Village. Qualitative method was used as research method by applaying interview technique, observation, and documentation to collect data and information. The results showed that traders who earned a living in Pasar Senin Rantau Panjang Kiri village helped the economy and improve their family welfare. It can be proved the increase of family income, owning a home, the fulfiment of food, the clothing is fulfilled even if only purchased when the need only, education of children who have been fulfilled, good health and recreation is fulfilled even if only a year only once and no savings for family needed. Internal factors that determine the level of family welfare the number of family members, shelter, social circumstances, and financial condition. The external factors was the people around the family.Keywords: Family Welfare, Small Traders, Pasar Senin